Analisis Kemitraan PT Simply Fresh Organic dengan Petani Sayuran Organik di Kabupaten Cianjur Jawa Barat (Jurnal Agribisnis Indonesia, 2023)
Partnership is relationship among two people or more that have purpose which is harmonious and form a deal for doing business together. Partnership also defined as a relationship cooperative relationship which gives profit to each other. Cooperation which is profit each other will give positive impact for business performer to continue developing and increasing business result that is done together. Partnership has important role for farmer who is difficult to sell his product farming. Partnership implementation by PT Simply Fresh Organic with organic vegetable farmer helps farmer in organic vegetable farming activity process. Such as, guarantee market which is available, capital assistance, development and production facilities by company that will help farmer to increase his income. The research aims to see: (1) Partnership pattern which is executed by PT Simply Fresh Organic with organic vegetable farmer, then will be seen category of partnership level relationship that is being intertwined. (2) To Analyze factors that influenced farmer is decision in partnership. The results of this research are: (1) Partnership pattern that is intertwined between PT Simply Fresh Organic with organic vegetable farmer is agribusiness operational partnership with degree of partnership in Prima Utama Partnership. (2) Factors which are significant or influential on farmer’s decision to partner are education factor and frequency of participating counseling.